2007
DOI: 10.1088/0957-0233/18/5/r01
|View full text |Cite
|
Sign up to set email alerts
|

Medical implants based on microsystems

Abstract: The fast development of CMOS technologies to smaller dimensions led to very high integration densities with complex circuitry on very small chip areas. In 2006 Intel fabricated the first products in a 65 nm technology. The cointegration of microsensors or actuators together with the very low power consumption of the CMOS circuitry is very well suited for use in implanted systems. Applications like intracranial or intraocular pressure measurements have become possible. This review presents an overview over actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…This methodology enables straightforward IOP sensing without involving further calculations which are derived from ocular mechanics as are used in applanation tonometry and which have large variation due to different dimensions and mechanical properties of individual eyes [7], [8]. In contrast to active sensing in which power transfer, size, and cost of the device are critical concerns [9], [10], passive sensing approaches have relatively flexible design constraints on the device side [11]. Works from many research groups have demonstrated the possibility of using miniaturized LC sensors (sensors with electrical LC resonant circuit) to enable passive wireless pressure sensing for various applications, including transcutaneous pressure monitoring, intracranial pressure monitoring, and pressure monitoring of abdominal aortic aneurysms in addition to the proposed IOP monitoring [12]- [17].…”
mentioning
confidence: 99%
“…This methodology enables straightforward IOP sensing without involving further calculations which are derived from ocular mechanics as are used in applanation tonometry and which have large variation due to different dimensions and mechanical properties of individual eyes [7], [8]. In contrast to active sensing in which power transfer, size, and cost of the device are critical concerns [9], [10], passive sensing approaches have relatively flexible design constraints on the device side [11]. Works from many research groups have demonstrated the possibility of using miniaturized LC sensors (sensors with electrical LC resonant circuit) to enable passive wireless pressure sensing for various applications, including transcutaneous pressure monitoring, intracranial pressure monitoring, and pressure monitoring of abdominal aortic aneurysms in addition to the proposed IOP monitoring [12]- [17].…”
mentioning
confidence: 99%
“…93, and the role of microsystems is described in Ref. 97. Many implanted devices require a wireless communication system with the outside environment 98 .…”
Section: Medical Implant/cathetersmentioning
confidence: 99%
“…The use of passive telemetry in implantable medical devices is common (Mokwa 2007) and enables the realization of active implants with no power constraints.…”
Section: Development Of a Novel Sensormentioning
confidence: 99%